2018
DOI: 10.1002/cmdc.201700694
|View full text |Cite
|
Sign up to set email alerts
|

Co‐administration of Antimicrobial Peptides Enhances Toll‐like Receptor 4 Antagonist Activity of a Synthetic Glycolipid

Abstract: This study examines the effect of co‐administration of antimicrobial peptides and the synthetic glycolipid FP7, which is active in inhibiting inflammatory cytokine production caused by TLR4 activation and signaling. The co‐administration of two lipopolysaccharide (LPS)‐neutralizing peptides (a cecropin A–melittin hybrid peptide and a human cathelicidin) enhances by an order of magnitude the potency of FP7 in blocking the TLR4 signal. Interestingly, this is not an additional effect of LPS neutralization by pept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…We have recently described the aggregation behavior of FP7 glycolipid, a related molecule to those described herein 51 . In particular, the analysis of the obtained NMR and TEM data (cryogenic and negative staining) permitted to show that FP7 forms micelle structures 36 . Indeed, previous investigations had demonstrated that FP7 has a CMC of about 9 µM 56 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have recently described the aggregation behavior of FP7 glycolipid, a related molecule to those described herein 51 . In particular, the analysis of the obtained NMR and TEM data (cryogenic and negative staining) permitted to show that FP7 forms micelle structures 36 . Indeed, previous investigations had demonstrated that FP7 has a CMC of about 9 µM 56 .…”
Section: Resultsmentioning
confidence: 99%
“…1) 25,33 or have a chemical structure unrelated to lipid A 34 . Eritoran and FP7 are the only lipid A mimetics whose direct binding to MD-2 and the competition with natural MD-2 ligands LPS and LOS have been reported 20,26,35,36 .
Figure 1Chemical structures. Natural E .
…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the synergy was observed also in a case where TLR4 was activated with lectins. DOSY NMR experiments and TEM microscopy images suggest a change in the supramolecular aggregation state of peptides caused by the interaction with FP7 ( 78 ).…”
Section: Glycolipid-based Tlr4 Modulatorsmentioning
confidence: 99%
“…The synergistic action of FP monosaccharides with antibacterial peptides neutralizing LPS was recently investigated ( 78 ). After LPS stimulation, FP7 was co-administrated to cells together with two anti-microbial peptides: cecropin A–melittin (CA–M) or LL-37, a human cathelicidin that binds to and neutralize LPS ( 79 , 80 ).…”
Section: Glycolipid-based Tlr4 Modulatorsmentioning
confidence: 99%
“…The combination of peptides with other classes of molecules is also of pharmacological interest, since synergism between two compounds can result in inactivation of the TLR4 receptor. These results were clarified by researchers that surveyed the combined action between the anionic glycolipid FP7 (diphosphorylated glucosamine monosaccharide) and cationic peptides, reporting that it can boost the activity of AMPs of the cecropin class ( Facchini et al, 2018 ). The results showed that cationic peptides can increase the activity of cecropin AMPs (cecropin A melittin).…”
Section: Antimicrobial Peptides Activity On Toll-like Receptormentioning
confidence: 99%